Influence of pre-slaughter capture chase duration stress on carcass and meat quality of indigenous chicken reared under traditional system in Bénin. - BONOU, ASSOUAN GABRIEL; AHOUNOU, GBÊNAGNON SERGE; SALIFOU, Saliou; BACHABI, FATIMA; PARAISO, FIDELE H.; KONSAKA, BERNADETTE M.; DAHOUDA, MOHAMADOU; DOUGNON, TOSSOU JACQUES; FAROUGOU, SOUAÏBOU; YOUSSAO, ALASSANE (My University, 2019)
Stress generally deteriorates meat quality. The current study aims to evaluate the influence of transportation and capture chase pre-slaughter stress on carcass and meat quality in local chicken of Benin. Sixty chickens of 8 to 10 months old divided into 3 flocks of 10 males and 10 females reared under traditional system were used. Chickens of the first flock were slaughtered after one hour of transportation by motorcycle, those of the second flock after 10 minutes of capture chase and the third one without pre-slaughter stress. Carcass and meat quality was evaluated. Carcass quality traits didn’t vary according to the pre-slaughter stress, except the thigh-drumstick weight that was higher with chased and transported chickens (P <0.05). Breast and thigh meat pH values of stressed chickens were higher (p <0.001). Drip loss and cooking loss didn't vary between flocks. Meat lightness was lower for the breast and the thigh of transported chickens on the slaughter day and at 24 hours post mortem (P <0.001). It was also lower in the thigh of the chased chickens at 24 hours after slaughter. The breast meat of stressed chickens was redder whereas their thigh meat showed the lowest values of the yellow index b * only at 24 hours. The meat shear force was the same for the three groups. The flavor, the juiciness, the tenderness and the global acceptance of the breast meat of the chickens didn't vary. Then, transportation and capture chase reduce the sensory and technological meat qualities of indigenous chicken.
Keywords: Indigenous chicken; Transportation; Capture chase; Meat quality; Benin.